TINJAUAN ASPEK KEAMANAN DAN KERAHASIAAN DOKUMEN REKAM MEDIS DI RUANG FILLING RUMAH SAKIT: STUDI LITERATUR - Syafhira Faradita Sari; Amir Ali (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2021)
The medical record file contains the value of confidentiality that must be maintained because the medical record contains the patient's medical history from the beginning to the end of the patient's treatment. Objecyive To maintain the security and confidentiality aspects of medical record documents in the hospital filing room. Methods Descriptive research with a qualitative research design, and using a literature study. Result this research Aspects of security and confidentiality of medical record documents in the hospital filing room are from the elements of Man, Money, Material, Machine, namely, the use of finger print in the filing room is still not optimal. Overview of the Security and Confidentiality of Medical Record Documents in the Hospital Filling Room is caused by the SOP for the lack of knowledge of the medical record officer, the storage room does not meet the standards, the DRM storage area does not use metal shelves.